Pengembangan Bisnis PT Anagile Kharisma Utama - Tan, Steven; Munir, Ningky Sasanti (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
The increase in the number of cashless transactions due to the shift in the way of public payments to cashless began to surge rapidly at the end of 2018, but the amount of EDC payments did not increase. The business model design & business development of PT Anagile Kharisma Utama is intended to take the opportunity of the phenomenon by placing POS (Point of Sales) and PG (Payment Gateway) in one device, namely EDC Android. Business model design & business development are analyzed using the Business Model Canvas approach. The results of the analysis are nine elements in the business model, which are customer segments, channels, customer relationships, value propositions, revenue streams, key resources, key activities, key partnerships, and cost structure.